Analisis Kesesuaian Tempat Penyimpanan Sementara Limbah Bahan Berbahaya dan Beracun (B3) Industri Manufaktur PT. Z - Anggreini, Wise Nutyara; Amalia, Aussie (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
In carrying out operational activities and equipment maintenance, PT. Z produces hazardous waste that requires proper management to prevent environmental pollution. This study aims to analyse the suitability of the Temporary Storage Site (TPS) for Hazardous Waste (B3) at PT. Z with the regulation of PermenLHK No. 6 of 2021. The method used in this study is scoring using the Guttman scale. The analysis results show that the existing condition of the Hazardous Waste TPS at PT. Z obtained a percentage score of 91.6% with a category of ‘Very Good’. Recommendations for improvement to enhance hazardous waste storage activities include replacing packaging and setting maximum filling limits for packaging.